Mosquito Larvicidal Constituents from the Ethanol Extract of Inula racemosa Hook. f. Roots against Aedes albopictus - Qing He; Xin Chao Liu; Rui Qi Sun; Zhi Wei Deng; Shu Shan Du; Zhi Long Liu (Journal of Chemistry)
The aim of this research was to determine larvicidal activity of the ethanol extract of Inula racemosa Hook. f. (Compositae) roots against the larvae of the Culicidae mosquito Aedes albopictus and to isolate any larvicidal constituents from the extract. Based on bioactivity-guided fractionation, 11,13-dihydroisoalantolactone (1), macrophyllilactone E (2), 5α-epoxyalantolactone (3), and epoxyisoalantolactone (4) were isolated and identified as the active constituents. Compounds 1 and 2 exhibited strong larvicidal activity against the early fourth-instar larvae of A. albopictus with LC50 values of 21.86 μg/mL and 18.65 μg/mL, respectively, while the ethanol extract had a LC50 value of 25.23 μg/mL. Compounds 3 and 4 also possessed larvicidal activity against the Asian tiger mosquitoes with LC50 values of 29.37 μg/mL and 35.13 μg/mL, respectively. The results indicated that the ethanol extract of I. racemosa and the four isolated constituents have potential for use in the control of A. albopictus larvae and could be useful in the search of newer, safer, and more effective natural compounds as larvicides.